Experimental and Numerical Investigations of Surge Extension on a Centrifugal Compressor with Vaned Diffuser Using Steam Injection - Chuang Gao; Weiguang Huang; Tianhua Zheng; Kang Yang; Haosen Yang; Yun Cao (International Journal of Rotating Machinery)
This paper presents the first report on surge extension with steam injection through both experimental and numerical simulation. The experimental section covers the test facility, instrumentation, and prestall modes comparison with and without steam injection. It is found that surge extension is not in proportion to injected steam. There exists an upper bound above which deteriorates the margin. Injection of less than 1% of the designed mass flow can bring about over 10% margin improvement. Test results also indicated that steam injection not only damps out prestall waves, but also changes prestall modes and traveling direction. At 90% speed, injection changed the prestall mode from spike to modal, while at 80% speed line, it made the forward traveling wave become backward. Through numerical simulation, location and number of injectors, molecular weight, and temperature of injected gas are modified to explore their influences on surge margin. Similar to the test results, there exists an upper bound for the amount of steam injected. The flow field investigation indicates that this bound is caused by the early trigger of flow collapse due to the injected steam which is similar to the tip leakage flow spillage caused spike stall in axial compressors.